(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-1-94-102 The article analyses the idiolect of the Spanish poet Luis Cernuda (Luis Cernuda; 1902-1963), in the context of interaction with cultural systems new to him. The author analyses the development of his career and points out some general correlations between the linguistic situation in emigration and the transformation of the poet’s idiolect. The elements of Luis Cernuda’s idiolect which allowed to create a linguistic image which could not be radically transformed are disclosed based on the analysed works and their means of expression. Key words: idiostyle, idiolect, emigration, cultural accommodation Acknowledgements: The study was carried out within the framework of research under a grant from the Russian Science Foundation (project No. 19-18-00429) at the Institute of Linguistics of the Russian Academy of Sciences